The Balassa-Samuelson Hypothesis in Developed Countries and Emerging Market Economies: Different Outcomes Explained - José García Solanes; Fernando Torrejón-Flores (Kiel Institute for the World Economy (IfW), 2008)
This paper studies the Balassa-Samuelson hypothesis in two areas with strong differences in economic development, sixteen OECD countries and sixteen Latin American economies. Applying panel cointegration and bootstrapping techniques that solve for cross-sectional dependence problems in the data, we find that the second stage of the hypothesis, which relates relative sector prices with the real exchange rate, only holds in the Latin American area. The failure of the latter in the OECD countries as a whole is reflected in departures from PPP in the tradable sectors, and is probably due to segmentation between national tradable markets.
Keywords: C15; F31; E31; 330; Balassa-Samuelson effect; bootstrapping techniques; cross-sectional dependence; economic development; exchange rate systems; Balassa-Samuelson Effekt; Wechselkurssystem; Entwicklung; Bootstrap-Verfahren; Vergleich; Entwicklungsländer; Schwellenländer; Aufstrebende Märkte